Evaluating the Ability of PRISM4 and PIM3 to Predict Mortality in Patients Admitted to Pediatric Intensive Care Unit; a Diagnostic Accuracy Study - Chegini, Victoria; Hatamabadi, Hamidreza; Jedari Attaran, Sima; Mahyar, Abolfazl; Mirzadeh, Monirsadat; Chegini, Venus (Archives of Academic Emergency Medicine, 2022)
Introduction : Limited resources and the large number of children in need of services in the pediatric intensive care unit (PICU) emphasize the need for effective allocation of resources for improving the outcome of at-risk patients. This study aimed to evaluate and compare the accuracy of PRISM4 and PIM3 systems in prediction of in-hospital mortality of patients admitted to PICU. Methods: The present retrospective cross-sectional study was a diagnostic accuracy study performed on patients admitted to PICU of Qods Hospital, Qazvin, Iran, during one year. Scores of PRISM4 and PIM3 scales were calculated for each patient using the available calculators, and the outcome of patients regarding in-hospital mortality was recorded. Finally, screening performance characteristics of the mentioned scales in prediction of patients’ mortality were calculated and reported. Results: 218 patients with the mean age of 40.68 ± 37.92 (2-160) months were studied (57.8% female). There was a significant direct correlation between PIM3 score and duration of stay in PICU (p < 0.0001; r = 0.259), need for inotropic drug administration (p = 0.001), and mortality rate (p = 0.001). In addition, area under the receiver operating characteristic (ROC) curve of PIM3 and PRISM4 in prediction of mortality among patients admitted to the PICU was 0.939 (95%CI: 0.880 – 0.998) and 0.660 (95%CI: 0.371 – 0.950), respectively (p = 0.001). Based on the findings, the best cut-off point for PIM3 scale in prediction of mortality was the score of 4 and it was estimated to be the core of 8 for PRISM4 scale. Sensitivity and specificity of PIM3 scale in prediction of mortality in the cut-off of 4 points were 100.00 (95% CI: 56.09- 100.00) and 81.51 (95% CI: 75.47- 86.38), respectively. These measures were 42.85 (95%CI: 11.80- 79.76) and 98.10 (95%CI: 94.89- 99.39) for PRISM4 model, which indicates the higher sensitivity of PIM3 system in this regard. Conclusion: based on the results of the present study, the accuracy of PIM3 is significantly higher than PRISM4 in prediction of in-hospital mortality among patients admitted to the PICU. It seems that considering the 100% sensitivity of PIM3 in prediction of outcome, this model is a better tool for screening patients who are at risk for in-hospital mortality in order to pay more attention and allocate more resources to improve their outcome.